A stochastic model of drought - KAMTE, P. P.; DAHALE, S. D. (MAUSAM, 1984)
The paper deals with an application of stochastic process to daily rainfall series of various meteorological sub-divisions and of different climatic regimes. An Auto-regressive AR(1) model is used to generate m-day minimum rainfall with the auto-correlations estimated through statistically transformed distribution of minimum rainfall of different durations. The model statisfactorily explains the observed minimum rainfall of different durations, Further, the probabilities of minimum rainfall of different durations are estimated to understand how best one can delineate the areas of droughts.